Strategy of Agribusiness Development of Chrysanthemum Flower in Pancasari Village, Sukasada District, Buleleng Regency - I Nyoman Rudianta; Anak Agung Ngurah Mayun Wirajaya (SEAS (Sustainable Environment Agricultural Science), 2018)
This study aims to identify and analyze internal and external factors on the development of chrysanthemum agribusiness in Pancasari Village, and to formulate alternative strategies and to determine the priority of agribusiness development strategy of chrysanthemum flowers in Pancasari Village. Determination of the location of the study using the method "purposive sampling", the basic method in this study is descriptive analysis, namely research based on actual problems that exist in the present. The results showed that the identification and analysis of internal factors on influencing variables of strength is the suitability of land and climate, the mastery of chrysanthemum flower technology, chrysanthemum agribusiness is a profitable business, chrysanthemum agribusiness is the main business of agricultural extension workers availability, cooperation between farmers in groups and experience of chrysanthemum agribusiness. While the identification and analysis of internal factors in the variables of weakness that influence the human resources of farmers are still low, the dependence of seedlings from Java/outside, limited land ownership/narrow, limited funds, limited facilities/infrastructure, lack of market information and poor farm management. Identification and analysis of external factors on the variables of opportunity that influence the availability of technology, the availability of markets, the availability of production facilities and equipment, agribusiness enterprises have bright prospects, regional autonomy, government policy and the availability of manpower. While external factors on threat variables that influence the unavailability of seeds at any time, pest and disease attacks, competition from Java/outside Bali, residential population, capital dependence on loan sharks, high land prices, and the lack of a pattern of partnership system. Chrysanthemum agribusiness development strategy in Pancasari Village is: General strategy is a growth strategy and stability. Alternative strategies are aggressive strategies and alternative strategies resulting from SWOT matrix analysis are: 1) Improve the quality and quantity of chrysanthemum flower production. 2) Improve farmer cooperation in groups, to minimize costs. 3) The use of production facilities and equipment. The strategy that should be implemented based on QSPM analysis is an intensive growth strategy.